The continued development of multiple supernumerary teeth: do they influence orthodontic treatment?. (2nd July 2021) - Oliver, Graham; Hamilton, Sean; Read, Natalie; Atack, Nikki
Abstract : Supernumerary teeth occur in approximately 1–2% of the population. Multiple supernumerary teeth are less common and usually associated with certain medical conditions. Most supernumeraries develop at a similar time to the normal series; however, this article describes the presentation and management of three patients who developed multiple supernumerary teeth during active orthodontic treatment in the permanent dentition. CPD/Clinical Relevance: These cases show development of multiple supernumerary teeth in the both the maxilla and mandible demonstrating a variation of types and effects on the dentition. In particular, multiple supernumeraries in the anterior maxilla and supplementals in the mandibular premolar regions highlight that supernumerary teeth may develop a considerable time after the development of the permanent dentition. These can develop during orthodontic treatment. Consideration, therefore, may be given to closer and longer monitoring of dental development in patients with multiple supernumerary teeth.